2019
DOI: 10.1016/j.jbi.2019.103122
|View full text |Cite
|
Sign up to set email alerts
|

Feature extraction for phenotyping from semantic and knowledge resources

Abstract: Objective: Phenotyping algorithms can efficiently and accurately identify patients with a specific disease phenotype and construct electronic health records (EHR)-based cohorts for subsequent clinical or genomic studies. Previous studies have introduced unsupervised EHR-based feature selection methods that yielded algorithms with high accuracy. However, those selection methods still require expert intervention to tweak the parameter settings according to the EHR data distribution for each phenotype. To further… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 57 publications
0
22
0
Order By: Relevance
“…Using the PRISM features, we PRISM features, we were able to train supervised self-learning (SSL) and transfer learning (STL) classifiers that resulted in AUC ROC of 0.97, which can be compared to the specialized computational phenotyping performances between 0.94 and 0.96 in the literature. 22 , 31 , 32 …”
Section: Resultsmentioning
confidence: 99%
“…Using the PRISM features, we PRISM features, we were able to train supervised self-learning (SSL) and transfer learning (STL) classifiers that resulted in AUC ROC of 0.97, which can be compared to the specialized computational phenotyping performances between 0.94 and 0.96 in the literature. 22 , 31 , 32 …”
Section: Resultsmentioning
confidence: 99%
“…Phenotyping features from the EHR have been traditionally culled and curated by experts to manually construct algorithms [7], but machine learning techniques present the potential advantage of automating this process of feature selection and refinement [8][9][10][11]. Recent machine learning approaches have also combined publicly available knowledge sources with EHR data to facilitate feature curation [12,13]. Additionally, while case and control phenotyping using EHR data has also relied on a small number of expert curated cohorts, recent studies have demonstrated that ML approaches can expand upon and identify such cohorts using automated feature selection and imperfect case definitions in a high-throughput manner [14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10][11] Recent machine learning approaches have also combined publicly available knowledge sources with EHR data to facilitate feature curation. 12,13 Additionally, while case and control phenotyping using EHR data has also relied on a small number of expert curated cohorts, recent studies have demonstrated that ML approaches can expand upon and identify such cohorts using automated feature selection and imperfect case de nitions in a high-throughput manner. [14][15][16][17][18] Studies have also shown that case and control selection with diagnosis codes can signi cantly affect model performance, the hierarchical organization of structured medical data can be utilized for feature reduction and model performance improvement, and calibration is essential for understanding the clinical utility of a phenotyping model.…”
Section: Introductionmentioning
confidence: 99%